Iowa RBA, August 31, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Iowa RBA for August 31, 1998. Highlights include Eurasian Collared Dove, and Red-breasted Nuthatch. Includes notes for updates for September 1, September 2, and September 4. Epson - sheet feed/flatbed